2018
DOI: 10.3389/fphar.2018.01165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Puerarin Regulated mTOR Signaling Pathway in Experimental Liver Injury

Abstract: It is known that excessive hepatocellular apoptosis is a typical characteristic of hepatic disease, and is regulated by the mammalian target of rapamycin (mTOR) signaling pathway. As the main active component of Kudzu (Pueraria lobata) roots, which is frequently used to treat hepatic diseases, Puerarin (Pue) has been reported to alleviate and protect against hepatic injury. However, it is unclear whether Pue can inhibit mTOR signaling to prevent excessive apoptosis in the treatment of hepatic diseases. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Puerarin is an isoflavone compound extracted from Pueraria lobata , a leguminous plant. It has been noted that puerarin has anti-inflammatory, anti-oxidation, anti-osteoporosis, hypoglycemic, and anti-cancer activities [46]. Puerarin inhibits cancer cells by regulating inflammation-related proteins and signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Puerarin is an isoflavone compound extracted from Pueraria lobata , a leguminous plant. It has been noted that puerarin has anti-inflammatory, anti-oxidation, anti-osteoporosis, hypoglycemic, and anti-cancer activities [46]. Puerarin inhibits cancer cells by regulating inflammation-related proteins and signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The MoA of these natural products is not corresponding to protection of skin barrier. However, several studies showed that these compounds, including puerarin, berberine, and wogonin, regulated the mammalian target of rapamycin (mTOR) and signal transducer and activator of transcription 3 (STAT3) [70][71][72][73][74][75]. The mTOR and STAT3 signaling pathways have been known as crucial for maintaining homeostasis of skin barrier in pathophysiology of atopic dermatitis [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Puerarin has been used clinically to treat a variety of diseases, such as cardiovascular disease, retinal arteriovenous obstruction, sudden deafness, diabetes, and diabetic complications (21,22). The pathogenesis of sarcopenia is associated with inflammation (23)(24)(25), oxidative stress (26,27), and myocyte apoptosis (28)(29)(30), and puerarin has anti-inflammatory, anti-oxidant, and apoptosisregulating effects (31). Thus, we conjectured that puerarin may have therapeutic effects in the treatment of sarcopenia.…”
Section: Introductionmentioning
confidence: 94%